2014
DOI: 10.1182/asheducation-2014.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in chronic lymphocytic leukemia and how they affect therapy choice: focus on NOTCH1, SF3B1, and TP53

Abstract: Chronic lymphocytic leukemia (CLL) is characterized by a relatively small number of recurrent genetic defects. These can be evaluated by clinically available methods such as fluorescent in situ hybridization and targeted sequencing approaches to provide data that can be very helpful in prognostication and planning of treatment. Acquired defects in the p53 pathway, activating mutations of NOTCH1, and dysfunctional mutations of SF3B1 and BIRC3 identify patients with higher risk of progressive disease, poorer res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
12
0
4
Order By: Relevance
“…Our study thus led us to propose that it might be primetime for a systematic evaluation of TP53 alteration through mutation and/or deletion as part of the prognostic pretreatment package of WM at diagnosis, in order to identify patients with TP53 Alt that might benefit more from BTK inhibitors (13). Interestingly, we observed the absence of mutations of ATM in our cohort suggesting different genomic features between CLL and WM (5,6). Similarly, we found no relationship (Continued.)…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Our study thus led us to propose that it might be primetime for a systematic evaluation of TP53 alteration through mutation and/or deletion as part of the prognostic pretreatment package of WM at diagnosis, in order to identify patients with TP53 Alt that might benefit more from BTK inhibitors (13). Interestingly, we observed the absence of mutations of ATM in our cohort suggesting different genomic features between CLL and WM (5,6). Similarly, we found no relationship (Continued.)…”
Section: Discussionmentioning
confidence: 61%
“…We thus investigated the effect of either of three compounds that showed activity in TP53 Mut condition, independently of the mechanism of loss of function of p53. Preliminary data showed the great interest for BTK inhibitors in relapsed WM and in CLL with TP53 alteration (6,13,26,35). We have evaluated the in vitro responses of WM to ibrutinib according to their TP53 status and showed that ibrutinib may induce apoptosis and loss of viability in WM, independently of p53 alteration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations